2001
DOI: 10.11150/kansenshogakuzasshi1970.75.851
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Influenza Vaccine in Health-care Workers

Abstract: We examined the effectiveness of trivalent influenza vaccine in reducing illness, absenteeism, and health care use among health-care workers (HCW) of Ishikawa Prefectural Central Hospital from December 1999 through March 2000. In recipients of vaccine (n = 132), the numbers of febrile illness, severe illness, febrile upper respiratory tract illness were significantly reduced compared with HCW without vaccination (n = 595). Use of prescription antibiotics and over-the-counter medications was also reduced. Influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Saxén and Virtanen, 7 in a randomized double-blind placebo-controlled study, showed that vaccination significantly reduced absenteeism related to respiratory infection. Nishi et al 2 and Susa et al 3 showed that influenza vaccine was effective in preventing influenzalike illness and reducing absenteeism. Harada et al 4 and Tomii et al 5 also showed vaccine efficacy in preventing febrile episodes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Saxén and Virtanen, 7 in a randomized double-blind placebo-controlled study, showed that vaccination significantly reduced absenteeism related to respiratory infection. Nishi et al 2 and Susa et al 3 showed that influenza vaccine was effective in preventing influenzalike illness and reducing absenteeism. Harada et al 4 and Tomii et al 5 also showed vaccine efficacy in preventing febrile episodes.…”
Section: Discussionmentioning
confidence: 98%
“…1 In Japan, however, there have been few studies to assess the vaccine efficacy in HCWs, and all the studies were based on clinical diagnoses. [2][3][4][5] However, influenza-like illness is not always influenza, and may include other febrile respiratory illness, whereas a rapid antigen detection kit for influenza shows a positive reaction for influenza. Such kits are widely used in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies prove the effectiveness of influenza vaccination in reducing illness absenteeism and improving health status among health care workers. 10…”
Section: Discussionmentioning
confidence: 99%
“…Influenza vaccine also reduced the reported days of absence from work. 14 The net effect was a reduction in cost to the provider, the patient, and generally the entire healthcare delivery system. We performed the present study to determine the current vaccination rates for our ED staff.…”
Section: Discussionmentioning
confidence: 99%